Non Hodgkin lymphoma presenting with adrenal insufficiency and bilateral huge adrenal masses - Huai, Heng Loh; Sukor, Norlela; AW, Norasyikin; M, Norlaila; O, Mohd Rahman; R, Subashini; Shahar, Mohammad Arif; Omar, Ahmad Marzuki; WS, Wan Juani; D, Azura; Ooi, CP; K, Nor Azmi (Malaysian Endocrine and Metabolic Society, 2014)
Adrenal involvement secondary to lymphoma is not commonly seen. We report a case of a 62-year old lady, with underlying hypertension on treatment, but otherwise healthy, presented with adrenal insufficiency with large bilateral adrenal masses, complicated with exudative left pleural effusion. She responded to intravenous hydrocortisone of 50mg tds. Computed tomography (CT) showed large heterogenous bilateral suprarenal masses (Figure 1, Figure 2). There were areas of necrosis with no calcification within the mass. Multiple lymphadenopathy in the abdominal region and mediastinum were noted. Lactate dehydrogenase level was elevated. Fungal and tuberculous cultures were negative. Trucut biopsy of the lesion showed Diffuse Large B cell Lymphoma. She was started on chemotherapy (Rituximab-CHOP). Secondary involvement of bilateral adrenal glands due to widespread lymphoma is not common, with Diffuse Large B cell Lymphoma being the most frequently seen. This is to highlight lymphoma as a possible cause of patient presenting with large bilateral adrenal masses and adrenal insufficiency.